An exploration of solutions for improving access to affordable fresh food with disadvantaged Welsh communities - Wang, Yingli; Touboulic, Anne; O'Neill, Martin (Elsevier, 2018)
Our research is rooted in community operational research (community OR) and adopts a qualitative problem structuring approach to exploring potential solutions for addressing inequality in access to affordable healthy food in disadvantaged communities in Wales, UK. Existing food provisions are synthesised and barriers to their effectiveness are identified. A portfolio of actions and commitment packages is co-developed with multiple stakeholders in order to bring about desired changes. Although these solutions address concerns specific to local Welsh communities, they can be generalised and applied in similar settings where food desert problems prevail. We draw upon insights from the literature on inequality, food deserts, and social capital to conceptualise the solutions around both material (providing and accessing) and social (reconnecting and strengthening) aspects. By addressing both material and social aspects simultaneously, we show how community-driven intervention can contribute to reducing inequality in disadvantaged communities. Our research experience reveals that COR is particularly effective in tackling a ‘wicked’ problem such as food deserts, and allows researchers to engage with communities, gain an understanding about the problematic situation and guide intervention efforts in a sustainable and systemic manner. A number of methodological reflections are offered as a way to contribute to the development of the field as a whole.